China's Development on New Energy Vehicle Battery Industry: Based on Market and Bibliometrics. Issue 1 (November 2020) - Zhang, Lei; Liu, Yingqi; Pang, Beibei
Abstract: The continuous deterioration of environmental problems and the energy crisis has prompted countries and regions to increase research and development and support for new energy vehicles (NEV). NEV's battery as the core components play an essential role in the cruising range and manufacturing cost in terms of energy, specific power, new materials, and battery safety. In order to know the development of NEV's batteries, as well as research hotspots and technology trends, this paper analyses the market performance and technology trend of China NEV's battery industry. Firstly, this paper analyses the policy and market, then clarify the macro environment of China's NEV battery industry development. Secondly, this paper uses CITESPACE software to analyze the scientific knowledge of the literature data, such as research hotspots, research institutions, and technology development trends. In the end, this paper proposes policy recommendations for the future development of China's NEV's battery industry from the perspectives of technology, market, and industrial chain.